Earthquake-resistant behavior of three mid-rise buildings designed according venezuelan seismic codes (Gaceta Técnica, 2016)
Here is presented a study on the seismic vulnerability of three mid-rise structural models projected according to Venezuelan seismic code Covenin 1756-01. Models have similar structural configurations in plant and in inter-story heights. Seismic action uses hybrid accelerograms compatible with the design spectrum characteristic of the metropolitan area Barquisimeto-Cabudare. Damage Evaluation is made through fragility curves and damage indices, including probabilistic approach. Some models showed high probability of severe damage or collapse, suffering significant stiffness degradation and lateral deformations beyond normative limits, showing that relative displacements and stiffness degradation are fundamental indicators for structural damage. It is concluded that to evaluate the behavior of the analyzed structural models subjected to probable seismic action, it ́s required a detailed study of the horizontal displacements, particularly relative displacements between levels and that the provisions of the Venezuelan seismic code may not be sufficient for evaluating the seismic performance of these models
Keywords: composite structures; damage models; dynamic analysis